2021
DOI: 10.1371/journal.pone.0247400
|View full text |Cite
|
Sign up to set email alerts
|

Insectivorous bats are less active near freeways

Abstract: Traffic disturbances (i.e. pollution, light, noise, and vibrations) often extend into the area surrounding a road creating a ‘road-effect zone’. Habitat within the road-effect zone is degraded or, in severe cases, completely unsuitable for wildlife, resulting in indirect habitat loss. This can have a disproportionate impact on wildlife in highly modified landscapes, where remaining habitat is scarce or occurs predominantly along roadside reserves. In this study, we investigated the road-effect zone for insecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In the present study, many insectivores considered rare were found roadkilled. The study by Bhardwaj et al (2021) pointed out that the activity of seven of ten insectivorous bats species decreased significantly within the proximity of a highway due to changes created in the surrounding environment by traffic, such as pollution, light, noise, and vibrations. The authors called the surrounding environment a "road effect zone, " and in this area, the habitat is degraded or entirely unsuitable for wildlife, which leads to an indirect loss of habitat (Bhardwaj et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, many insectivores considered rare were found roadkilled. The study by Bhardwaj et al (2021) pointed out that the activity of seven of ten insectivorous bats species decreased significantly within the proximity of a highway due to changes created in the surrounding environment by traffic, such as pollution, light, noise, and vibrations. The authors called the surrounding environment a "road effect zone, " and in this area, the habitat is degraded or entirely unsuitable for wildlife, which leads to an indirect loss of habitat (Bhardwaj et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We used 1000 as the road cost value for the five reptile resistance surfaces based on well‐documented negative road effects on turtles and snakes (Garrah et al., 2015 ; Paterson et al., 2019 ; Robson & Blouin‐Demers, 2013 ). Few studies have examined road impacts for Henslow's Sparrow and Northern Long‐eared Bat specifically, but data from closely related species suggest strong behavioral avoidance of roads but unclear mortality risk (Benítez‐López et al., 2010 ; Bennett & Zurcher, 2013 ; Bhardwaj et al., 2021 ; Cooke et al., 2020 ). As a result, we assigned a road cost value of 500 for these two species.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined road impacts for Henslow's Sparrow and Northern Long-eared Bat specifically, but data from closely related species suggest strong behavioral avoidance of roads but unclear mortality risk(Benítez-López et al, 2010;Bennett & Zurcher, 2013;Bhardwaj et al, 2021;Cooke et al, 2020).…”
mentioning
confidence: 99%
“…This could explain the low occupancy levels of bat boxes in the Iberian Peninsula where it is around 40% (Poulton 2006;Alcalde et al 2020; Sánchez-Poveda 2022). Indeed, there is an increased risk since wind energy will develop greatly (Serrano et al 2020), where the species which use bat boxes will be threatened by these infrastructures (Roemer et al 2017;Bhardwaj et al 2021).…”
Section: Other Considerations About An Uncontrolled Bat Boxes Policy ...mentioning
confidence: 99%